Occurrence and distribution of epipelic and epilithic diatoms in batman stream (Turkey) - Sonmez, Feray; Asan, Keziban (My University, 2012)
In this study, the seasonal variations in distribution and abundance of epipelic and epilithic diatoms were investigated at 4 stations selected on Batman Stream between April and September 2009. Sampling was performed monthly, and water temperature, electrical conductivity, pH and concentrations of total dissolved solid matter, dissolved oxygen, total hardness, organic matter, nitrite, nitrate, total nitrogen, phosphate, total phosphorus, sulphate, silica and chlorophyll-a were measured and analysed. Diatoms (Bacillariophyta) were the most important algal group in Batman Stream, in terms of number of species and abundance. A total of 49 diatom taxa were identified. Navicula, Cymbella, Nitzschia and Gomphonema were richest in species numbers. The taxon numbers in epipelon were higher than those recorded in epilithon. Cymbella affinis, Cyclotella ocellata and Diatoma vulgare occurred with higher individual numbers in epilithon whilst C. affinis, Tabularia fasciculata and Ctenophora pulchella were more conspicuous in epipelon. Batman River has got Class I in water quality according to the Water Quality Criteria.
Keywords: Batman Stream; Diatom; Epilithon; Epipelon; Turkey